Re-enterprising the unplanned urban areas of Greater Cairo- a social innovation perspective. Issue 2 (28th May 2021) - Nicolopoulou, Katerina; Salama, Ashraf M.; Attia, Sahar; Samy, Christine; Horgan, Donagh; Khalil, Heba Allah Essam E.; Bakhaty, Asser
Abstract : Purpose: This study aims to develop an innovative and comprehensive framework to address water-related challenges faced by communities located in urban settlements in the area of Greater Cairo. It is commonly accepted that such global challenges that border issues of resilience, community development, social equity and inclusive growth, call for a collaboration of disciplines. Such collaboration allows for the identification of synergies in ways that can enlighten and enrich the space of potential solutions and create pathways towards robust solutions. Design/methodology/approach: The research process has been participatory, and it involved, apart from site interviews, engagement via a photographic exhibition, during an outreach and engagement event, of the researched sites in one of the academic institutions of the authors. A total of 12 women were interviewed and the expert's workshop was attended by 12 experts. Findings: Social innovation can promote agile processes to prototyping services, involving multiple sectors and stakeholders through open ecosystems. For urban settlements undergoing rapid expansion, social innovation can help communities and governments to build resilience in the face of resource gaps – often making use of advancements in technology and improvements from other disciplines (Horgan and Dimitrijevic, 2019). For the unplanned urban areas around Greater Cairo, input from different knowledge areas can offer valuable contributions; in terms of the project and the study that we report on in this paper, the contributing areas included architecture and urban planning, as well as women-led entrepreneurship targeting economic growth, social and community impacts. Originality/value: In this paper, we demonstrate the significance of a transdisciplinary framework based on social innovation, for the study of women-led entrepreneurship as a response to water-based challenges within an urban settlement. The creation of such a framework can be a significant contribution to conceptualise, examine and respond to "wicked challenges" of urban sustainability. This paper also believes that the readership of the journal will be subsequently benefitting from another way to conceptualise the interplay of theoretical perspectives at the level of organisations and the individual to support the inquiry into such challenges.